Synthesis And Characterization Of Zinc Oxide Nanorods Sensitised By In2S3, Pbs And In2S3-Pbs For Photoelectrochemical Application - Almamari, Mohammed Rashid Obaid (2022)
This study focuses on the synthesis and characterisation of zinc oxide nanorods sensitised by narrow bandgap energy metal chalcogenides for photoelectrochemical application. In this study, ZnO nanoparticles seed layer (NPs) was prepared by RF Magnetron sputtering and sol-gel spin coating technique, followed by heat-treatment at different temperatures to optimise the nucleation. ZnO nanorod arrays (NRAs) were then grown through a simple, facile hydrothermal method on the optimised seed layer sample. The effect of hydrothermal growth duration was optimised to ensure achieving the high aspect ratio of ZnO NRAs. In2S3/ZnO NRAs/ITO and PbS/ZnO NRAs/ITO were prepared using successive ionic layer adsorption and reaction (SILAR) method. In addition, considering the effect of various parameters on formation of In2S3/ZnO NRAs and PbS/ZnO NRAs nanocomposite, the synthesis was carried out with variation in number of SILAR cycles, dipping time, concentration of cationic precursor, and annealing temperature. The formation of ZnO nanorods and In2S3 was noticed when the colour of the samples changed from colourless to white for ZnO, and yellow for In2S3/ZnO. The powder X-ray diffraction (XRD) analysis verified that the synthesised ZnO NRAs sample has hexagonal phase, whereas In2S3 has tetrahedral crystal structure. The deposited photosensitiser has no effect on the host material structure.